ISOlASI DAN ELUSIDASI SENYAWA KIMIA DARI KULIT POHON Garcinia tetrandra PIERRE - Soleh Kosela; leonardus B. Kardono; M. Hanafi (Jurnal Kimia Terapan Indonesia, 2000)
A preliiminary study was carried out to isolate theconstituents of the stem bark of Garcinia tetran dra Pierre(Guttiferae). Several species of this family had been known asmedicinal herb, some other contain bioactive constituents andnovel compounds. The isolation were carried out by macerationin n-hexane where crude extract was purified usingchromatographic technique on SIG60 coloumn and n- hexane ethylacetate as eluents by gradient. Two pure compunds werefound and their molecular structures were determined on thebasis of combined spectroscopic methods UV, IR, 1H-NMR, l3C-NmR and MS and comparison with literature. The compouridhad been identified as xanton, 15-hydroxy-20, 21, 22, 23-tetramethyl-3H,11H-dipyrano (3, 2-a ; 2'. 3'-i) xanten-17-one(A), known as Thwaitesixanton and a triterpene as Hopenol - a(Hop-(22) (29)-en 3-0 ol) (B).